Dichloroacetate and Salinomycin Exert a Synergistic Cytotoxic Effect in Colorectal Cancer Cell Lines - Skeberdytė, Aistė (Sci Rep, 2018)
In the present study, we examined a hypothesis that dichloroacetate, a metabolic inhibitor, might efficiently potentiate the cytotoxic effect of salinomycin, an antibiotic ionophore, on two human colorectal cancer derived cell lines DLD-1 and HCT116. First, we performed a series of dose response experiments in the 2D cell culture by applying mono- and combination therapy and by using the Chou-Talalay method found that salinomycin in combination with dichloroacetate acted synergistically in both cell lines. Secondly, in order to recapitulate the in vivo tumor architecture, we tested various doses of these compounds, alone and in combination, in the 3D multicellular spheroid culture. The effect of combination of dichloracetate and salinomycin on multicellular spheroid size was stronger than the sum of both monotherapies, particularly in HCT116 cells. Further, we demonstrate that the synergistic effect of compounds may be related to the inhibitory effect of dichloroacetate on multidrug resistance proteins, and in contrast, it is not related to dichloroacetate-induced reduction of intracellular pH. Our findings indicate that the combination therapy of salinomycin and dichloroacetate could be an effective option for colorectal cancer treatment and provide the first mechanistic explanation of the synergistic action of these compounds.